Students English Language Learning Strategies - Neman, Meily Ivane Esther (8ISC Abstract Proceedings, 2022)
This quantitative descriptive study aims at finding out the strategies in learning English used by students in Universitas Klabat. It is also to describe the differences between male and female students in using strategies in learning English and the type of strategies that are mostly used by the students. The respondents were the students from Business English classes enrolled in semester II 2020/2021 with a total of 91 students. The instrument used in this study is the SILL questionnaire which consists of 50 items and six categories, which are cognitive, metacognitive, affective, memory, and social strategies. The result shows that the students from Business English classes mostly use Cognitive Strategies, Compensatory Strategies, and Metacognitive Strategies in learning English. Based on gender, Female students used mostly metacognitive strategies, while male students mostly used cognitive strategies. For overall strategies, item 15 from cognitive strategies (I watch English language TV shows spoken in English or go to movies spoken in English) is highly used by all students with a mean score of 4.43. Item 43 from affective strategies (I write down my feelings in a language learning diary) is used with the lowest frequency level with a mean of 2.19. From the six categories of strategies, the students mostly used cognitive strategies. Keywords : Strategies in Learning English, SILL, Language Learning